Women’s lived experiences of menstrual stigma in Türkiye: a descriptive phenomenological study - Ayşe Nur Yilmaz; Sümeyye Altiparmak (BMC Public Health, 2026)
Abstract Methods A descriptive phenomenological qualitative design was employed to explore the lived experiences of women regarding menstrual stigma. Twenty-eight women aged 18–49 years from seven geographical regions of Türkiye were purposively recruited through menstruation-related social media platforms and participated in semi-structured online interviews. Participants shared their personal experiences regarding menstruation and strategies for coping with menstrual stigma. Descriptive statistics were analyzed using SPSS 22.0, while qualitative data were analyzed in MAXQDA 2020 using an inductive thematic analysis. Codes were generated from the interview transcripts and subsequently organized into categories and overarching themes. Results Six main themes emerged: (1) Religious and Cultural Beliefs as Drivers of Menstrual Stigma, (2) Social Norms as Drivers of Menstrual Secrecy and Shame, (3) Psychological and Social Consequences of Menstrual Stigma, (4) Challenging Menstrual Stigma through Communication and Empowerment, (5) Strategies for Reducing Menstrual Stigma and Promoting Menstrual Health, (6) Educational and Professional Consequences of Menstrual Stigma. Taken together, these themes illustrate that menstrual stigma operates as a multidimensional social phenomenon that permeates women’s religious, psychological, educational, and professional lives, while also revealing their active efforts to challenge and transform stigmatizing norms. Conclusion This study demonstrated that menstrual stigma in Türkiye is deeply rooted in religious beliefs, cultural traditions, and gendered social norms, compelling women to conceal menstruation and affecting their psychological well-being, educational experiences, and professional lives. Although participants actively challenged these stigmatizing norms through open communication and social media advocacy, the findings underscore the need for culturally sensitive public health interventions, comprehensive menstrual health education, and policies that promote menstrual equity and reduce stigma.